SIMPULAN BAHASA MASYARAKAT MELAYU SARAWAK : SATU ANALISIS SEMANTIK INKUISITIF - SAIDATUL NISHA, ABDUL SALAM (2020)
A idiom is an expression that consists of two or more words and has a spesific meaning. The objective of this study was to identify the meaning of idioms implicit in Sarawak Malay, analyze the meaning implicit in Sarawak Malay idioms and analyze intelligence and intelectuality in the creation of the Sarawak Malay idioms. This study only focuses on vocabulary idioms Malay Sarawak Lundu, Sarawak. Two residents from Lundu district, Sarawak selected to be informants to the researcher in conducting this study. 15 vocabulary idioms Sarawak Malay selected by data but only 10 Sarawak Malay idioms are analyzed using semantic inquisitive (SI). To complete this study, the researcher uses the theory that can underline this study, namely Relevant Theory by Sperber and Wilsons (1986,1996). The results show that the selection of each word in idioms can be associated with a personality that existed at the Sarawak Malay Community.